PUBLIC OFFICIAL’S PERSONAL BRANDING ON SOCIAL MEDIA (Content Analysis on DediMulyadi Fan Page Timeline on October 2017) - Anisa Atsilah; Yenni Sri Utami; Sigit Tripambudi (The Indonesian Journal of Communication Studies, 2018)
Personal branding using social media often used by public officials. Dedi Mulyadi is one of the public official that uses social media to do his personal branding. This research’s purpose is to identify personal branding on Dedi Mulyadi’s Fan Page Account on October 2017. Researcher explains this research using planning theory, new media concept, and personal branding concept. This research type is content analysis with quantitative method. Result of this research shows that content on Dedi Mulyadi fan page account’s timeline dominated by writing, video, and picture. Words that are used in the fan page are well-mannered, using Bahasa Indonesia or native language. The themes are about politics, economy, culture, environment, religion, health, tourism, social, sports, livestock, and combination of the stated topics. All the contents picture 8 concepts of personal branding. Dedi Mulyadi presents himself as an official who is skilled, religious, nationalist, humble, close with local culture, wise, and decisive. Dominant personal branding shown by Dedi Mulyadi as public official who is religious and nationalist could be seen on Purwakarta. Facilities that were built there and his advice to his city focus on religion and nationalism.